Lagrangian Sensor Particles for detecting hydrodynamic heterogeneities in industrial bioreactors: Experimental analysis and Lattice-Boltzmann simulations - Sebastian Hofmann; Ryan Rautenbach; Lukas Buntkiel; Isabel Sophie Brouwers; Lena Gaugler; Jonas Barczyk; Jürgen Fitschen; Sebastian Reinecke; Marko Hoffmann; Ralf Takors; Uwe Hampel; Michael Schlüter (Chemical Engineering Journal Advances)
This study analyzes trajectories of three particle types in an industrial-scale bioreactor, equipped with a Rushton turbine and a pitched blade turbine, to characterize hydrodynamic compartments. The trajectories obtained from measurements with Lagrangian Sensor Particles (LSP,exp) are compared to those generated by Lattice-Boltzmann large eddy simulations (LB LES). The latter method is used to reproduce analogous simulated LSPs (LSP,sim) as resolved particles. Additionally, for benchmarking purposes, massless tracer particles (tracer,sim) are incorporated to accurately represent fluid flow dynamics. Discrepancies in the axial probability of presence and velocity between LSP,exp and LSP,sim likely stem from differences in mass distribution, density, number of particles, and ratio of particle size to grid. A necessarily high LSP,sim volume fraction in LB LES leads to increased collisions and clustering, negatively impacting flow dynamics, and reducing turbulent kinetic energy by at least 3%. Circulation and residence time distributions for the three types of particles identify three hydrodynamic compartments within the bioreactor, validated by local mixing time distributions. The ratio of overall average circulation time to global mixing time is Θglob,95≈3.0⋅t¯circ for LSP,exp, which largely corresponds to literature results. A theoretical LSP size of dp,th≈1mm is estimated to be flow following on micro-scale in the bulk phase, if a Stokes number of St=0.1 is assumed. However, Stokes number estimations confirm that LSP,exp are capable to follow flow patterns on the meso-scale and macro-scale with St≈0.2 and St≈0.002, respectively. Hence, hydrodynamic structures at length scales greater than or equal to the size of the impeller can be investigated by current state-of-the-art LSPs, which proves their technological readiness for industrial bioreactors.